PELATIHAN MEMBATIK ECOPRINT BANGKITKAN UMKM di DESA NAPAL PUTIH - Abdulah Abdullah; Tri Wiyoko; Zulqoidi R Habibie; Zikrillah Zikrillah; Adinda Yuli Sella (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Ecoprint batik training activities were held in the desa Napal Putih, kecamatan Serai Serumpun, kabupaten Tebo. This activity is in the form of training and direct assistance for UMKM. This training activity invited PKK mothers from Napal Putih Village. The initial stage in this activity is to know the constraints and efforts made by UMKM actors. Then proceed with the process of socialization and training in the form of theory and practice then conduct training directly at the UMKM location. Based on the activities that have been carried out, MSMEs can be encouraged to improve their abilities and develop their creativity to innovate in making eco print batik. In carrying out this activity, it received a good response from the community and village officials as partners. Judging from the amount of enthusiasm and support given during the activity. The results of this activity are expected to be able to encourage the level of the economy and creative entrepreneurial activities in the desa Napal Putih which will also be able to influence the process of empowering human resources and provide added economic value to the community.